Medico-legal perspectives on sudden cardiac death in young athletes - Oliva, A.; Grassi, V. M.; Campuzano, O.; Brion, M.; Arena, V.; Partemi, S.; Coll, M.; Pascali, V. L.; Brugada, J.; Carracedo, A.; Brugada, R. (International Journal of Legal Medicine, 2017)
Sudden cardiac death (SCD) in a young athlete represents a dramatic event, and an increasing number of medico-legal cases have addressed this topic. In addition to representing an ethical and medico-legal responsibility, prevention of SCD is directly correlated with accurate eligibility/disqualification decisions, with an inappropriate pronouncement in either direction potentially leading to legal controversy. This review summarizes the common causes of SCD in young athletes, divided into structural (hypertrophic cardiomyopathy, arrhythmogenic cardiomyopathy, congenital coronary artery anomalies, etc.), electrical (Brugada, congenital LQT, Wolf-Parkinson-White syndrome, etc.), and acquired cardiac abnormalities (myocarditis, etc.). In addition, the roles of hereditary cardiac anomalies in SCD in athletes and the effects of a positive result on them and their families are discussed. The medico-legal relevance of pre-participation screening is analyzed, and recommendations from the American Heart Association and European Society of Cardiology are compared. Finally, the main issues concerning the differentiation between physiologic cardiac adaptation in athletes and pathologic findings and, thereby, definition of the so-called gray zone, which is based on exact knowledge of the mechanism of cardiac remodeling including structural or functional adaptions, will be addressed.